Characterising dispersed metal plumes in surficial soils and sediments in the Irish Midlands: Using isotope fingerprints to develop vectors in mineral exploration - KALVERAM, ANN-KRISTIN (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2018)
The enhancement of mineral exploration is essential for the growing demand of base metals in the world. Successful geochemical surveys in soil and till have led to numerous discoveries. However, most of these deposits are shallow and situated in areas unaffected by anthropogenic activities. Exploring for more deeply buried mineralisation, and in areas such as anthropogenic influenced lands offer new challenges for mineral exploration. This thesis demonstrates geochemical investigations to advance mineral exploration tools and their implications, using the example of the Ballinalack carbonate-hosted Zn-Pb deposit in the Irish Midlands, Ireland. Sulphide samples (sphalerite and pyrite) were texturally characterised using SEM imaging technique and afterwards analysed by in situ laser ablation ICP-MS to understand proximal-distal fingerprints within the mineralisation lens and their elemental pool. Furthermore, a trace element as well as Cu and Zn isotope approach have been applied to surficial sediments (soil and till) to understand how elevated concentrations of trace elements can be detected and transported above a shallowly (1.5 m) and deeply buried (150 m) sulphide lens in an area affected by former glaciation and modified by agricultural practices. The trace element signature of the sulphides at Ballinalack consists of Ag, As, Co, Fe, Ga, Hg, Mo, Ni, Pb, Sb and Zn, among others, which broadly coincide with elevated concentrations of Pb, Cd, As, Ag, Tl, Zn, Sb and Ba in soil and till above the shallowly buried sulphide mineralisation. Any overprint from glaciation or active agriculture-pasture, would seem to be minimal; however, the deeply buried mineralisation was not detected by trace-element analyses of the overlying soil/till. These findings contradict the prevailing reduced chimney model for the transport of elements towards the surface. The anomalous soil and till concentrations of trace elements mentioned above can be spatially associated by heavy δ65 Cu and light δ66 Zn isotope signatures; the heavy Cu isotope signatures reflect direct weathering of the sulphides resulting in the soil anomaly. The Zn isotope signature may indicate that sphalerite is also a source of the trace-elemental anomaly and hence the mineralisation in the underlying bedrock is the source of the fingerprint in the soil and till. Accordingly, this approach confirms the feasibility of stable metal isotopes for use as an additional tool in mineral exploration.
APPROVED
Keywords: till; trace elements; soil; mineral exploration; non-traditional stable isotopes; sulphides